Effects of Combined Endurance and Resistance Training in Women With Multiple Sclerosis: A Randomized Controlled Study - Correale, Luca; Buzzachera, Cosme Franklim; Liberali, Giulia; Codrons, Erwan; Mallucci, Giulia; Vandoni, Matteo; Montomoli, Cristina; Bergamaschi, Roberto (Frontiers in Neurology, 2021)
PURPOSE: To test the hypothesis that combined resistance and endurance training would improve muscle strength, fatigue, depression, and quality of life in persons with MS. METHODS: Twenty-seven women with MS were randomly assigned to either control (CON, n = 13) or the experimental (EXP, n = 14) group. The participants in the EXP group trained twice a week for 12 weeks, followed by 12 weeks of detraining. Both CON and EXP groups were tested before and after 12 weeks of the intervention period, as well as 12 weeks after training cessation (follow-up), where measures of muscle strength, fatigue, depression, and quality of life were evaluated. RESULTS: There were pronounced changes in maximal voluntary isometric contraction (MVIC), 1RM leg extension, and 1RM chest press following the intervention period in the EXP group (P < .05), but not in the CON group (P > .05). These changes persisted after 12 weeks of detraining. Similar findings were found for fatigue, depression, and physical and mental composites of quality of life. CONCLUSION: These results suggest that combined exercise training, at a minimum, prevents the disease-related deterioration of muscular performance and quality of life and well-being in persons with MS.